2014
DOI: 10.1021/jf503413f
|View full text |Cite
|
Sign up to set email alerts
|

Labeling Milk along Its Production Chain with DNA Encapsulated in Silica

Abstract: The capability of tracing a food product along its production chain is important to ensure food safety and product authenticity. For this purpose and as an application example, recently developed Silica Particles with Encapsulated DNA (SPED) were added to milk at concentrations ranging from 0.1 to 100 ppb (μg per kg milk). Thereby the milk, as well as the milk-derived products yoghurt and cheese, could be uniquely labeled with a DNA tag. Procedures for the extraction of the DNA tags from the food matrixes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…Recent work has tested the usage of such tags in the food supply chain by delivering exogenous DNA fragments within a coat of silica, a common food additive, at an extremely low cost. It has been shown that these tags could be used to trace the source of milk in dairy products such as yogurt (Bloch et al 2014) and serve as a long-term authentication mark of premium olive oil (Puddu et al 2014). Moving forward, artificial DNA labels can create an edible data structure that includes the type of food, producer, lot number, nutrient information, and presence of known allergens or simply encode a URL to a webpage that contains this information.…”
Section: Food Industrymentioning
confidence: 99%
“…Recent work has tested the usage of such tags in the food supply chain by delivering exogenous DNA fragments within a coat of silica, a common food additive, at an extremely low cost. It has been shown that these tags could be used to trace the source of milk in dairy products such as yogurt (Bloch et al 2014) and serve as a long-term authentication mark of premium olive oil (Puddu et al 2014). Moving forward, artificial DNA labels can create an edible data structure that includes the type of food, producer, lot number, nutrient information, and presence of known allergens or simply encode a URL to a webpage that contains this information.…”
Section: Food Industrymentioning
confidence: 99%
“…One simple method would be through standardized watermarking of genetically engineered organisms [42,43]. Furthermore, DNA barcoding can serve as a valuable method for tracking food and agricultural products for authentication and safety concerns [44]. …”
Section: Dna Communicationmentioning
confidence: 99%
“…In our previous work we have shown that silica particle detection is compatible with DNA, but accessible detection limits have been > 10'000 particles per analysis,15 still far away from the potential PCR analytics has to offer. To reach the goal of detecting single nanoparticles, we had to significantly improve the synthesis of DNA comprising particles to yield individual, non-agglomerated sub 100 nm particles.…”
mentioning
confidence: 97%